Mindfulness-Based Versus Story Reading Intervention in Public Elementary Schools: Effects on Executive Functions and Emotional Health - Milaré, Claudete A. R.; Kozasa, Elisa H.; Lacerda, Shirley; Barrichello, Carla; Tobo, Patricia R.; Horta, Ana Lucia D. (Frontiers in Psychology, 2021)
Introduction In this study we compared the effects of a mindfulness-based intervention (MBI) with a story reading intervention (SI) on the executive functions and psychological profile of children in two different public schools in São Paulo, Brazil. Methods In this controlled clinical trial, 207 children aged 8 to 9 years old responded to the Five-Digit Test (FDT), stress levels, depression, anxiety, positive and negative affect, at baseline (T0) and 8 weeks later (T1). From T0 to T1, school 1 participated in MBI classes and school 2 in IS classes. Results In school 1 (MBI), children improved their scores on all tests except reading (errors) and counting (errors) compared with school 2. No differences were observed between groups in terms of emotional health. Conclusion It is feasible to implement MBI or SI in Brazilian public schools. Students in the MBI group presented broader effects in executive functions, while students in the SI group showed a trend toward reduced negative affect and depression symptoms.